Enzymatic degradation of sulphonated azo dye using purified azoreductase from facultative Klebsiella pneumoniae - Dixit, Shweta; Garg, Sanjeev (Folia microbiologica, 2021)
Heterologously expressed and purified azoreductase enzyme from facultative Klebsiella pneumoniae was used to degrade sulphonated azo dye. Methyl orange (MO) was used as the model dye to study the azo dye decolorization potential of the purified enzyme at different conditions. The enzyme had maximum activity at 40 °C and pH 8.0. The enzyme was observed to be thermo-stable as some enzyme activity was retained even at 80 °C. The apparent kinetic parameters, i.e., appKm and appVmax, for azoreductase using MO as a substrate were found to be 17.18 μM and 0.08/min, respectively. The purified enzyme was able to decolorize approximately 83% of MO (20 μM) within 10 min in the presence of NADH. Thus, efficient decolorization of MO was observed by the purified enzyme. The recombinant enzyme was purified approximately 18-fold with 46% yield at the end of four steps of the purification process. Enzyme was present in a tetrameric structure as confirmed by the volume at which protein was eluted in gel filtration chromatography, and the monomeric molecular mass of enzyme was found to be 23 kDa on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The dye degradation efficiency of azoreductase cloned from Klebsiella pneumoniae and purified from recombinant Escherichia coli was observed to be much higher as compared with the efficiencies of the reported azoreductases from other bacterial strains. In the present study, we report the purification and characterization of the azoreductase cloned from Klebsiella pneumoniae and expressed in Escherichia coli.
Keywords: Coloring Agents; Temperature; biodegradace; molekulová hmotnost; teplota; Klebsiella pneumoniae; Nitroreductases; Escherichia coli; Recombinant Proteins; Biodegradation, Environmental; bakteriální proteiny; azosloučeniny; rekombinantní proteiny; Kinetics; barvicí látky; Hydrogen-Ion Concentration; Azo Compounds; Bacterial Proteins; nitroreduktasy; koncentrace vodíkových iontů; kinetika; Molecular Weight